The prevalence of obesity and the factors affecting obesity in the students of secondary education - Gokosmanoglu, Feyzi; Cengiz, Hasret; Varim, Ceyhun; Yaylaci, Selcuk; Nalbant, Ahmet; Karacaer, Cengiz (International Journal of Research in Medical Sciences, 2019)
Background: Childhood obesity has reached alarming dimensions all around the world. In this study, our objective is to determine the prevalence of childhood obesity in the secondary education as well as genetic, cultural and environmental factors giving rise to obesity, nutritional habits, family history and activity status. Methods: The research was performed on 750 students aged between 14-18. Body Mass Index (BMI= weight/height2 (kg/m²)) and Relative Body Mass Index (Rel BMI) values of each child were calculated by making use of their height and weight measurements. An evaluation was made through the use of a questionnaire form consisting of 46 questions that questioned the family history, nutritional habits and activity status of the children at issue. Results: About 41.7% of 750 children incorporated into the study were female, whereas 58.2% of them were male. The age distribution was between the age range, 14-18. According to BMI values, 12.3% of the children were overweight, while 4% of them were obese. According to Relative BMI values, on the other hand, 10.4% of the children were overweight, whereas 12.9% of them were obese. When the children’s nutritional habits, activity status and family history were evaluated, we ascertained that doing physical exercises irregularly, consuming pastry foods at home and the presence of obesity history within the family had all led to the development of obesity as well as being overweight (p <0.05). Conclusions: In these research subjects comprising children of secondary education, we showed that the nutritional habits, cultural nutritional differences and the insufficiency in physical activities as well as the genetic susceptibility in children could be the determinants in obesity development.